Diagnosis of Coxiella burnetii endocarditis by using nanopore targeted sequencing: a case report - Xinsheng Yan; Qimei Wei; Tingting Liu; Dong Wang; Zhenlu Zhang (BMC Infectious Diseases)
Abstract Background Infective endocarditis (IE) can be caused by a variety of pathogens, including bacteria, fungi, and atypical pathogens. The diversity of IE manifestations contributes to diagnostic uncertainty, which can lead to missed diagnoses and inappropriate treatment. Diagnosing Coxiella burnetii endocarditis is particularly challenging, as routine blood cultures often yield negative results and echocardiography seldom reveals vegetations. In recent years, the rapid development of sequencing technology provides a new direction for the diagnosis of IE. Case presentation The present study reports the case of a 57-year-old male patient who was admitted with a diagnosis of severe aortic stenosis. Cardiac computed tomography (CT) angiography revealed a diastolic aortic valve malformation with significant leaflet thickening, calcification and pseudoaneurysm formation, the etiology of which was considered to be due to infectious possibilities. Although clinical suspicion of infective endocarditis was raised, since echocardiogram did not reveal any vegetations and blood cultures were negative, the etiology remained unclear and empirical drug therapy was used. The patient exhibited a severe inflammatory reaction after aortic valve replacement. Samples were sent for pathogenic testing again, including blood cultures and blood nanopore targeted sequencing (NTS). The other tests were all negative, only the NTS detected C. burnetii. After further confirmation, the final diagnosis was C. burnetii infective endocarditis. The patient was subsequently discharged from the hospital after demonstrating improvement with targeted treatment. One month post-discharge, a follow-up examination indicated that he had recovered well. Conclusion This case study demonstrates the accurate diagnosis and treatment of C. burnetii endocarditis through NTS analysis of blood samples. As a novel technology, NTS may play an important role in the diagnosis of culture-negative infections caused by unidentified pathogens.